7-3(5t-7)=67

Simple and best practice solution for 7-3(5t-7)=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3(5t-7)=67 equation:


Simplifying
7 + -3(5t + -7) = 67

Reorder the terms:
7 + -3(-7 + 5t) = 67
7 + (-7 * -3 + 5t * -3) = 67
7 + (21 + -15t) = 67

Combine like terms: 7 + 21 = 28
28 + -15t = 67

Solving
28 + -15t = 67

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + -15t = 67 + -28

Combine like terms: 28 + -28 = 0
0 + -15t = 67 + -28
-15t = 67 + -28

Combine like terms: 67 + -28 = 39
-15t = 39

Divide each side by '-15'.
t = -2.6

Simplifying
t = -2.6

See similar equations:

| 5x^2y^4-80x^4y^2=0 | | 1=23*t+2-1-2+1-23*t+2*t-1*t | | 23*t+2-1-2+1-23*t+2*t-1*t=1 | | 2w^2-5w-88=0 | | 2x-6+5=11 | | 3x-1-4=1 | | (-5y^3/8y^4)*(64y^6/25y) | | 3056890000-15000000x=3000000 | | 2n^3-32n=0 | | 1/3(9k-6)=7 | | 3a-4b=14 | | 2sinX+X=0 | | sinx+x=0 | | 6/2/3=18/N | | 830+840+380+380= | | 3/8m=9 | | 13.95x+8=15.95x | | D=175+70t | | D=175+70 | | D=175+-70 | | -9(t+4)=36 | | 27+3y-6=11y-9-2y | | D=175+-70t | | x+18+4x=-30-4x-33 | | 24y=14y-8 | | 4r^6+15r^3-25=0 | | 14q^2-33qb+18b^2=0 | | -3(x-1)+8(x-3)=6x+7+-5x | | 50a^4+60a^2-20=0 | | 5a^4+6a^2-2=0 | | -7r+3t-8s-5r+12s+14r+5s-11r= | | 2s^2-7s-4=0 |

Equations solver categories